KESADARAN HUKUM MASYARAKAT KABUPATEN TEGAL TERHADAP PENDAFTARAN HAK ATAS TANAH - Bha'iq Roza Rakhmatullah (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2018)
The registration of land rights in the Land Office has a time limit. This paper discusses about why the community of Tegal Regency has not yet had legal awareness to the registration of land rights transfer, how the legal effect on the delay of registration of land rights transfer based on the purchasing deed of the Making Land Deed Official by the receiving party rights, and how to solve public legal awareness and solutions to land registration delays. The method used in this research is by the Socio-Legal approach that is an approach which is done or used to be a reference in highlighting the problems of applicable legal aspects. the community of Tegal Regency, especially the weak economic community have not yet had legal awareness to register the transfer of land rights based on purchasing deed of the Making Land Deed Official to Tegal Regency Land Office. Suggestion from this research is The existence of strict enforcement of sanctions to unscrupulous officials of the Land Office who make irregularities, all stakeholders make a memorandum of understanding together in the context of registration of the transfer of land rights, revision of article 40 paragraph (1) Government Regulation Number 24 the Year 1997.Keywords: Land Rights Transfer, delay, Community Legal Awareness